Open study

is now brainly

With Brainly you can:

  • Get homework help from millions of students and moderators
  • Learn how to solve problems with step-by-step explanations
  • Share your knowledge and earn points by helping other students
  • Learn anywhere, anytime with the Brainly app!

A community for students.

use separation of variables to solve the initial value problem. dy/dx=(cos x)e^(y+sinx) and y=0 when x=0

See more answers at
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly


Get your free account and access expert answers to this and thousands of other questions

\[e^{-y} dy =\cos(x)e^{\sin(x)} dx\]
integrate both sides
Lol.. I don't know how to move "the x with dx" and "y with dy".. :/ can you show me that part?

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

i multiplied dx on both sides
\[e^{y+\sin(x)}=e^{y} e^{\sin(x)}\]
divide both sides by e^y
Oh ok. Thanks.
How do I integrate cosxe^(sin x) dx?
ley u=sin(x) => du=cos(x) dx
? What about the e? Do I put e to the u power?
\[\int\limits_{}^{}e^u du=e^u+C=e^{\sin(x)}+C\]
i replace sin(x) with u and cos(x) dx with du
Oh? But don't I integrate |dw:1327549907891:dw|? What happens with the cos...
cos(x) dx=du i replaced cos(x) dx with du i did integrate
Ohh I see. Ok, what do I do now? Do I plug in the given x, y values to find C?
have you integrated the other side yet?
I have now: -e^(-y) = e^(sinx) + C
ok so enter in (0,0) and solve for C
I solved that C = 0, So does the equation become -e^(-y) = e^(sinx) ?
-1=1+C -1-1=C -2=C
Oh I forgot about the negative on the left.
Then -e^(-y) = e^(sinx) - 2 ?

Not the answer you are looking for?

Search for more explanations.

Ask your own question